(untitled) (The Review of Diabetic Studies, 2025)
Background: Thyroid hormones play a critical role in regulating cardiovascular physiology. Dysregulation, whether overt or subclinical, has been linked to arrhythmias, heart failure, atherosclerosis, and metabolic disturbances. Understanding these associations is crucial for early risk stratification and clinical intervention. Objective: To systematically review observational and Mendelian randomization studies examining the relationship between thyroid dysfunction and cardiovascular diseases (CVDs). Methods: Following PRISMA 2020 guidelines, electronic databases including PubMed, Scopus, Web of Science, Embase, and Google Scholar were searched for studies published between 2016 and 2025. Studies assessing serum thyroid hormones (TSH, FT3, FT4), subclinical or overt thyroid disease, or genetically predicted thyroid function and cardiovascular outcomes were included. Both cross-sectional, cohort, and Mendelian randomization designs were considered. Data extraction focused on sample characteristics, thyroid measures, cardiovascular outcomes, and effect estimates. Quality was assessed using the Newcastle–Ottawa Scale and MR-specific criteria. Results: Ten studies were included, encompassing >1.5 million participants across global cohorts. Low thyroid function correlated with adverse cardiovascular health metrics and metabolic risk factors (Fang et al., 2024; Bai et al., 2025; Neves et al., 2022). Hyperthyroid tendencies, indicated by low TSH or high FT4, were causally linked to atrial fibrillation (Larsson et al., 2019; Ellervik et al., 2019). MR analyses showed protective effects of mild hypothyroidism against stroke (Marouli et al., 2020) but no consistent relationship with ischemic heart disease (Zhao & Schooling, 2017). Hormone replacement therapy required careful titration to avoid over- or under-replacement, impacting cardiovascular outcomes (Evron et al., 2022; Stamatouli et al., 2020). Conclusions: Thyroid dysfunction, including subclinical states, has significant implications for cardiovascular health. Both metabolic and arrhythmic pathways mediate this risk, emphasizing the need for early detection, individualized monitoring, and multidisciplinary management.